Impact of fujimorist autocracy in the diplomatic service of the Republic (1990-1995) - Carrillo Piraquive, Carlos (2018)
This article is the result of a research that aimed to analyze the relationship that was established between the Fujimorist Autocracy and the Diplomatic Service of the Republic after the mass cessation of 117 career diplomats. For this purpose, a set of publications that appeared in the main newspapers of national circulation were used. Open interviews were made to diplomatic officers of the Foreign Ministry. Memorandas, Institutional Letters, Circulars of internal character, that is, sources of first hand, among others, were reviewed. All these materials were used as in the Case Study method to approach this institution as a central unit of analysis and therefore unveil its organizational transformation. For this, the political neoinstitutionalism was used as a theory, which allowed us to see that the institution adapted itself to the new changes to guarantee its own survival at the expense of legitimizing a type of foreign policy that embraced neoliberal reforms and at the same time covered up a corruption complaint on a case of embezzlement.